The Urgency of Digital Forensics in Investigating the Criminal Offense of Disseminating False News at Cirebon City Police Resort - Nur Abida Yasvin; Waluyadi Waluyadi (Journal of Law and Social Politics, 2026)
Background: The rapid advancement of information technology has transformed communication and information dissemination, particularly through digital platforms and social media. However, this progress has also increased the risk of cybercrime, including the spread of false news. Objective: This study analyzes the urgency of digital forensics in investigating the criminal offense of disseminating false news, or hoax, through digital platforms at the Cirebon City Police Resort (Polresta Cirebon), with a specific focus on investigative capacity and constraints under the framework of the Electronic Information and Transactions Law (ITE Law). Methods: This study employs a normative juridical approach supplemented by empirical field interviews. It analyzes the role of digital forensics in collecting and examining electronic evidence under Law Number 1 of 2024 concerning the Second Amendment to the ITE Law. Primary data were obtained through structured interviews with two investigators at Polresta Cirebon, while secondary data were derived from legal literature and statutory regulations. Results: Digital forensics is critically needed to trace digital footprints, verify the authenticity of hoax content, reconstruct dissemination chains, and strengthen the admissibility of electronic evidence in court. The key challenges include limited access to overseas servers, perpetrator anonymity through encryption, rapid changes in digital content, a shortage of trained investigators at the Polres/Polsek level, and insufficient forensic laboratory infrastructure. Conclusion: This study recommends the establishment of specific digital forensic regulations, grassroots forensic investigation teams, ISO/IEC 17024- and ISO/IEC 17025-certified personnel and laboratories, and cross-platform international cooperation mechanisms to enhance ITE.